Understanding STEM academics' responses and resilience to educational reform of academic roles in higher education - Pauline Mary Ross; E. Scanes; P. Poronnik; H. Coates; W. Locke (SpringerOpen, 2022)
Abstract Background Across the globe, there have been significant reforms to improve STEM education at all levels. A significant part of this has been teacher reform. While the responses and resilience of STEM teachers to educational reforms in secondary education have received significant attention, the responses and resilience of STEM teachers in higher education remains understudied. In higher education, educational reforms of academic roles have seen increasing numbers of STEM academics focussed on education. Responses of STEM academics to education reform of the academic role have some parallels with teacher resilience, but there are also potential misalignments within a culture which values and prioritises science disciplinary research. This study examined the responses of STEM academics in higher education to educational reform of the academic role using the theoretical construct of resilience and Bronfenbrenner's socio-ecological model. This was a 2-year case study of 32 academics and senior educational leaders in higher education in STEM. Data collection included semi-structured interviews which were theme coded and inductively analysed. Results The responses and resilience of STEM academics focussed on education appeared to be dependent on interactions between individual disposition in the microsystem and influences of the exosystem and the external macrosystem. Five major themes emerged about the value and quality, scholarship and expertise, progress and mobility, status and identity and community and culture of STEM academics focussed on education. The exosystem was a significant unidirectional influence on STEM academics where judgements were made concerning academic performance, awards, and promotion. Responses of senior leaders in the exosystem were influenced by the macrosystem and culture of science. Academics focussed on research, rather than education were more valued and more likely to be both financially rewarded and promoted. Conclusion During this pressured decade, where COVID-19 has intensified stress, more attention on the direction and reciprocal relationships in the socio-ecological model of higher education is needed in order for educational reform in higher education STEM to be effective. Resilience of STEM academics to educational reform in higher education is a dynamic quality, and the capacity to "bounce back", learn from challenges, and realise expectations of educational reform will depend on an understanding of resilience and support of Bronfenbrenner's spheres of influence.